CFD simulation of flow distribution in the randomly packed bed Dixon ring. Issue 12 (13th August 2022) - Amini, Younes; Shadman, Mohammad Mahdi; Karimi-Sabet, Javad
ABSTRACT: The maldistribution in randomly packed beds with a high diameter ratio is a result of wall-flow formation and channeling. In this study, the thin randomly packed bed (dp /D = 1/8) filled with Dixon ring is simulated with a porous media model. The motivation of our study is to understand the effect of surface tension and liquid inlet velocity on the height of the wall-flow formation. Furthermore, the flow structure in this packed bed was described by numerical simulation. The results show that increasing the liquid inlet velocity and surface tension causes a faster distribution of liquid flow that led to faster formation of wall flow. Increasing the surface tension from 0.05 to 0.07 N/m causes the lower wall-flow formation from 0.19 m to 0.15 m in liquid velocity of 0.015 m/s and 0.09 to 0.06 in liquid velocity of 0.08 m/s. According to the findings, the 30% increasing the surface tension (from 0.07 N/m to 0.085 N/m) led to 30% decreases in height of wall-flow formation in the case of lower liquid velocity (0.015 m/s) and 50% decreases in the height of wall-flow formation in case of higher liquid velocity (0.08 m/s).